Age-dependent increases of calcium, phosphorus, and sodium in the uterine arteries of thai - Nutcharin Ongkana (2018)
To elucidate compositional changes of the uterine artery with aging, the authors investigated age-related changes of elements in the uterine arteries of Thai. After ordinary dissection by medical students at Chiang Mai University was finished, the uterine arteries were resected from Thai subjects. Thai subjects ranged in age from 27 to 86 years (average age∈=∈63. 3∈±∈17.7 years). The element content of the uterine arteries was analyzed by inductively coupled plasma-atomic emission spectrometry. It was found that the Ca, P, and Na contents increased progressively in the uterine arteries of Thai with aging. A significant accumulation of Ca and P in the uterine arteries of Thai was found in the sixties patients, and the accumulation increased markedly in the seventies. Regarding the uterine arteries in subjects more than 60 years, the extent of accumulation of Ca and P in the uterine arteries of Thai was one half of that in the uterine arteries of Japanese. Regarding the relationships among elements, extremely significant direct correlations were found among the contents of Ca, P, Mg, Zn, and Na in the uterine arteries of Thai. As Ca increased in the uterine arteries of Thai, P, Mg, Zn, and Na increased simultaneously in the arteries. © 2008 Humana Press Inc.